The stock price behavior of chinese markets : a preliminary study - Ang, Fui Siong (2014)
The emergence of the Chinese equity markets provides new opportunities for investors to participate in the economic boom in China. These markets exhibit high expected returns as well as high volatility. This research examines the daily return behaviour of the four China share indices: the Shanghai A-share Index, the Shanghai B-share Index, the Shenzhen A-share Index, and the Shenzhen B-share Index. By using daily data of these share indices from March 1993 to December 1994, the results show that weak form efficiency does not exist in the Bshare markets. Segmentation is found between the two B-share markets but not the A-share markets. This gives evidence that macro-economic factors of China affect the two A-share markets concurrently. There is evidence that the returns of the A-share indices lead the returns of the B-share indices. As for the two A-share markets, it is found that the Shenzhen A-share returns lead the Shanghai A-share returns but not vice versa. Both the B-share returns are shown to have bi-directional lead-lag relationship. This research further extends the analysis between the B-share indices with the Standard and Poor's 500 Index and the Hang Seng Index. No correlation exis ts between the China markets and the two foreign markets. It is found that the returns of the foreign markets do not lead the B-share markets.